GelMA Encapsulated DPSCs and HUVECs for Dental Pulp Regeneration. - Khayat, Arwa. (2017)
Abstract: Pulpal revascularization is commonly used in the dental clinic to obtain apical closure of immature permanent teeth with thin dentinal walls. Although sometimes successful, stimulating bleeding from the periapical area of the tooth can be challenging, and in turn may deleteriously affect tooth root maturation. Our objective here was to define reliable methods to regenerate pulp-like tissues in tooth root segments (RS) injected with human Dental Pulp Stem Cells (hDPSCs) and Human Umbilical Vein Endothelial Cells (HUVECs) encapsulated in 5% Gelatin Methacrylate (GelMA) hydrogel. RS injected with acellular GelMA alone and empty RS were used as controls. Combined hDPSCs and HUVECs (1:1) were encapsulated in 5% GelMA and injected into root segments (RS) of 6mm length and 2-3mm orifice wide. White Mineral Trioxide Aggregate (WMTA) was used to seal one of the orifices while the other was left open. Samples were cultured in-vitro in osteogenic media for 13 days, and subsequently implanted subcutaneously in nude rats for 4 and 8 weeks. At least five (5) sample replicates were used for each experimental and control groups. Analyses of harvested samples found that pulp-like tissues formed in hDPSC/HUVEC encapsulated GelMA filled RS, and that host cell infiltration was observed in the acellular GelMA and empty RS groups. Mesenchymal Stem cells and endothelial cells were identified using immunofluorescent IF for Vimentin and CD31, and hDPSCs and HUVECs were distinguished from host cells using IF for anti-rh-Mitochondrial antibody. Our results showed that GelMA supported hDPSC/HUVEC proliferation and organization, and also demonstrated the ability to attract and provide attachment for host cells. GelMA hydrogels promoted the establishment of host vasculature within the segments, and extracellular matrix (ECM) deposition. Together, these results identify GelMA hydrogel as a promising alternative therapy for clinically relevant pulpal revascularization.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Other.; Advisor: Pamela Yelick.; Committee: Nelson Monteiro, Elizabeth Smith, and Sarah Pagni.; Keyword: Dentistry.